2002
DOI: 10.1002/cne.10439
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Slack potassium channel in the rat central nervous system

Abstract: The Slack gene encodes a voltage-dependent K(+) channel that has a unitary conductance of approximately 60 pS. Evidence from heterologous expression studies suggests that Slack channel subunits can also combine with the Slo subunit to generate Ca(2+)-activated K(+) channels of larger conductances. Nonetheless, the function of Slack in the brain remains to be identified. We have now generated an affinity-purified antibody against the N-terminal of rat Slack, for biochemical and immunohistochemical studies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(220 citation statements)
references
References 52 publications
9
210
1
Order By: Relevance
“…Using a previously characterized antibody against Slack channels (Bhattacharjee et al, 2002), we found Slack immunoreactivity in all types of rat DRG neurons (Fig. 1).…”
Section: Ubiquitous Slack Expression In Adult Drg Neuronsmentioning
confidence: 82%
See 1 more Smart Citation
“…Using a previously characterized antibody against Slack channels (Bhattacharjee et al, 2002), we found Slack immunoreactivity in all types of rat DRG neurons (Fig. 1).…”
Section: Ubiquitous Slack Expression In Adult Drg Neuronsmentioning
confidence: 82%
“…Then sections were incubated with a mixture of primary antibodies in PBS containing 5% BSA overnight at 4°C. Primary antibodies included mouse antineurofilament antibody (1:400; Millipore Bioscience Research Reagents), calcitonin gene-related peptide (CGRP) antibody (1:2500; Sigma), and chicken anti-Slack antibody (1:1000) (Bhattacharjee et al, 2002). After several rinses, secondary antibodies Alexa Fluor 633 goat anti-mouse, Alexa Fluor 488 goat anti-rabbit, and Alexa Fluor 546 goat anti-chicken were added (1:1000) for 2 h. Coverslips were then mounted on slides using Prolong Gold antifade reagent with 4Ј,6Ј-diamidino-2-phenylindole dihydrochloride.…”
Section: Methodsmentioning
confidence: 99%
“…Neurons were permeabilized with 0.1% Triton X-100 for 4 min and then washed again in PBS. Neurons were incubated with an anti-Slack antibody (1:1000) (Bhattacharjee et al, 2002) at 4°C overnight followed by a secondary AlexaFluor 546 goat anti-chicken antibody (1:1000) for 2 h at room temperature. After three washes in PBS, coverslips were then mounted on slides and imaged.…”
Section: Methodsmentioning
confidence: 99%
“…All groups of mice reacted strongly to a loud acoustic stimulus with the exception of the 8-month-old C57BL/6 and the 8-month-old DBA/2J animals, which showed little or no response. Immunohistochemistry was performed as described previously (Bhattacharjee et al, 2002). Anti-CREB and anti-pCREB were purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%